Al-Attas on Intelect and It’s Relevance to The Islamization of Knowledge: Sufism philosophical Approach - Mudin, Moh.Isom; Desnafitri, Andin (Khatulistiwa, 2019)
The intellect has two aspects such as cognitive or theoretical intellect (‘alimah) and active or practical intellect (‘amilah). This cognitive intellect have four aspect such as material intellect (al-‘aql al-hayulani), possible intellect (al-‘aql al-mumkin) or possessive intellect (al-‘aql bi’l malakah) or intellect in action (al-‘aql bi’l-fi’l), potential intellect (al-‘aql al-quwwah), and acquired intellect (al-‘aql al-mustafad) called by the holy spirit (al-ruh al-Quds). the intellect function as the aspect of soul such as the vegetative (al-nabatiyyah), the animal (al-hayawaniyah) and the human (al-insaniyyah) or the rational (al-nathiqah). Syed Muhammad Naquib Al-Attas take the important step to solve this problem and analyze the linguistic problem as the one step to perform the Islamization of contemporary knowledge which developed with the key of Islamic term concept as intellect